2014
DOI: 10.1111/tpj.12628
|View full text |Cite
|
Sign up to set email alerts
|

The condensin complexes play distinct roles to ensure normal chromosome morphogenesis during meiotic division in Arabidopsis

Abstract: Meiosis is a specialized cell division essential for sexual reproduction. During meiosis the chromosomes are highly organized, and correct chromosome architecture is required for faithful segregation of chromosomes at anaphase I and II. Condensin is involved in chromosome organization during meiotic and mitotic cell divisions. Three condensin subunits, AtSMC4 and the condensin I and II specific subunits AtCAP-D2 and AtCAP-D3, respectively, have been studied for their role in meiosis. This has revealed that bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 83 publications
(181 reference statements)
8
31
0
Order By: Relevance
“…Consistent with the RNA-seq data, the expression of several condensin genes (CAP-D2, CAP-D3, CAP-H, and CAP-H2) was significantly reduced in mmd1 meiocytes compared with the wild type ( Figure 7B), with CAP-D3 showing the greatest reduction ( Figure 7B). In previous studies, Arabidopsis CAP-D3 was localized to chromatin in mitotic cells (Schubert et al, 2013;Smith et al, 2014). We therefore performed immunofluorescence experiments in meiocytes and found that the level of CAP-D3 protein was significantly lower in mmd1 chromosomes than in the wild type (Figure 8), providing additional evidence that supports a role for MMD1 in regulating meiotic condensation, in part by affecting CAP-D3 expression levels.…”
Section: Mmd1 Regulates Cap-d3 Expression Likely By Directly Binding supporting
confidence: 57%
See 3 more Smart Citations
“…Consistent with the RNA-seq data, the expression of several condensin genes (CAP-D2, CAP-D3, CAP-H, and CAP-H2) was significantly reduced in mmd1 meiocytes compared with the wild type ( Figure 7B), with CAP-D3 showing the greatest reduction ( Figure 7B). In previous studies, Arabidopsis CAP-D3 was localized to chromatin in mitotic cells (Schubert et al, 2013;Smith et al, 2014). We therefore performed immunofluorescence experiments in meiocytes and found that the level of CAP-D3 protein was significantly lower in mmd1 chromosomes than in the wild type (Figure 8), providing additional evidence that supports a role for MMD1 in regulating meiotic condensation, in part by affecting CAP-D3 expression levels.…”
Section: Mmd1 Regulates Cap-d3 Expression Likely By Directly Binding supporting
confidence: 57%
“…Previous studies in Arabidopsis showed that condensin proteins have a role in the frequency of meiotic recombination (Smith et al, 2014). We thus examined the recombination frequency in the wild type and mmd1 by counting the chiasmata number at diplotene (Figure 4).…”
Section: The Mmd1 Mutation Has a Slight Effect On Meiotic Crossover Fmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutations in condensin genes lead to major developmental defects in plants (Liu et al, 2002;Siddiqui et al, 2003;Siddiqui et al, 2006). Although the biological function of condensin in plant meiosis remains elusive, recent studies in Arabidopsis have revealed its role in maintaining normal meiotic chromosome integrity (Schubert et al, 2013;Smith et al, 2014). Chromosome structure and higher-order configuration appear to be closely related to cell cycle progression during meiosis.…”
Section: Introductionmentioning
confidence: 99%